Perbandingan Efisiensi Boiler Awal Operasi Dan Setelah Overhaul Terakhir Di Unit 5 PLTU Suralaya - Roswati Nurhasanah; Orlando Firdaus (Sekolah Tinggi Teknik - PLN, 2016)
The boiler is functioning equipment turn the water into steam by heating. Existing plants are specified in the supply of electrical energy required by konsumen.Effisiensi is one of the many parameters used to assess whether or not the performance of a boiler.Metode used in the calculation of boiler efficiency is the input-output method and heat losses by the aim of knowing the cause of the decrease in efficiency. Suralaya boiler efficiency analysis unit 5 meliputianalisaawaloperasidananalisasetelah terakhir.Dari overhaul both the analysis of these calculations will be elaborated based on the method of heat losses, thus resulting to a conclusion after comparison. Based on the analysis, the efficiency of the boiler when the last overhaul lower than initial efficiency of development. From the calculation of the authors analyzed the causes of decline in the efficiency and the conclusion of the decline 0.71% boiler efficiency and operation early last overhaul.